PREFERENCE BASED TERM WEIGHTING FOR ARABIC FIQH DOCUMENT RANKING - Khadijah Fahmi Hayati Holle; Agus Zainal Arifin; Diana Purwitasari (Jurnal Ilmu Komputer dan Informasi, 2015)
In document retrieval, besides the suitability of query with search results, there is also a subjective user assessment that is expected to be a deciding factor in document ranking. This preference aspect is referred at the fiqh document searching. People tend to prefer on certain fiqh methodology without rejecting other fiqh methodologies. It is necessary to investigate preference factor in addition to the relevance factor in the document ranking. Therefore, this research proposed a method of term weighting based on preference to rank documents according to user preference. The proposed method is also combined with term weighting based on documents index and books index so it sees relevance and preference aspect. The proposed method is Inverse Preference Frequency with Î± value (IPFÎ±). In this method, we calculate preference value by IPF term weighting. Then, the preference values of terms that is equal with the query are multiplied by Î±. IPFÎ± combined with the existing weighting methods become TF.IDF.IBF.IPFÎ±. Experiment of the proposed method uses dataset of several Arabic fiqh documents. Evaluation uses recall, precision, and f-measure calculations. Proposed term weighting method is obtained to rank the document in the right order according to user preference. It is shown from the result with recall value reach 75%, precision 100%, and f-measure 85.7% respectively.